2018
DOI: 10.1007/s10705-018-9959-x
|View full text |Cite
|
Sign up to set email alerts
|

Web-based tool for calculating field-specific nutrient management for rice in India

Abstract: Site-specific nutrient management (SSNM) can be an alternative to a recommendation for uniform fertilizer use across a rice (Oryza sativa L.) production system within a country or region of a country. We developed a web-based decision support tool named Nutrient Manager for Rice (NMR), which used principles of SSNM to calculate fertilizer N, P, and K rates for individual fields based on a target yield set for each field. It also used expected growth duration of the rice variety, crop establishment method, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…The sand content was negatively correlated with the clay content, CEC, and available K ( Figure 1); that is, a high sand content decreased the soil's ability to retain nutrients. Our finding that rice yield in the unfertilized plots strongly reflected the inherent soil fertility or nutrient-holding capacity agrees with previous studies (Homma et al, 2003;Sharma et al, 2019). As White et al (2000) suggested, the Toul Samroung soil proved to be the most fertile of the three soil groups used in this study, probably because of its high clay and CEC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The sand content was negatively correlated with the clay content, CEC, and available K ( Figure 1); that is, a high sand content decreased the soil's ability to retain nutrients. Our finding that rice yield in the unfertilized plots strongly reflected the inherent soil fertility or nutrient-holding capacity agrees with previous studies (Homma et al, 2003;Sharma et al, 2019). As White et al (2000) suggested, the Toul Samroung soil proved to be the most fertile of the three soil groups used in this study, probably because of its high clay and CEC.…”
Section: Discussionsupporting
confidence: 92%
“…This would lead to a significant K deficit when adequate N and P inputs were provided. The soil nutrient status determined by basic soil analysis such as that in the present study may not always be associated with the rice yield (Banayo et al, 2018a;Sharma et al, 2019) because simple estimates of plant-available nutrient contents cannot always predict their relationship with plant nutrient uptakes (Dobermann and Fairhurst, 2000). Our results support those in previous studies of soil-specific nutrient management for Cambodian rice, but clearly suggest that there is an opportunity for upgrade.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It was unique for each field trial and served as the RCM treatment. RCM typically set the target yield higher than the historical yield reported by the farmer during the RCM interview, but RCM also adjusted target yield downward when transplanting was delayed beyond a critical date, and RCM limited upward adjustment in yield for low-yielding rice varieties (Sharma et al, 2019). As a result, target yield was less than historical yield reported by the farmer in 12% of the field trials in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Field-specific fertilizer recommendations calculated by NMR increased yield and net income compared to the existing farmers’ fertilizer practice in on-farm research with irrigated rice in southern India (Sharma et al, 2019). Sharma et al (2019) also compared NMR to an existing recommendation for a blanket application of fertilizer in the absence of soil testing. NMR recommendations did not increase yield compared to the blanket fertilizer recommendation (BFR), but NMR reduced fertilizer cost and risk of financial loss and increased fertilizer use efficiency compared to BFR.…”
Section: Introductionmentioning
confidence: 99%